Transferable decision-making procedure for integrated flood management: A theoretical approach to the micro studies of human decision-making and decision makers heuristics - Tuck Fatt Siew (Albert-Ludwigs-Universität Freiburg, Institut für Forstökonomie, 2008)
The development and implementation of a transferable decision support system (DSS) for environmental or natural resources management has been a great challenge. The management problems dealing with both natural and social processes are fundamentally bound with complexity and uncertainty. This has resulted in the much recognised interfacing and integration problems of scientific outputs into decision-making process and these problems have been subjected to contradictory debates too. In this conjunction, holistic and integrated approaches are still required for the understanding of the elements that underlie the complex situations and subsequently for addressing the interfacing and integration problems in order to improve the applicability and transferability of DSS. The main purpose of this working paper is to primarily compile and analyse literature and the state-of-the-art pertaining to these issues, so as to provide a setting and framework for the research project. The ultimate aim of the research project is to develop a transferable decisionmaking procedure through the integration of knowledge production and use (or soft and hard systems) in the field of integrated flood management and thus to promote cooperation and consensus between different actors. A theoretical approach is adopted in this study. The concept of systems thinking is used for the understanding of the complex decision-making system that underlies the complex situations. Complex decision problems are analysed based on the concept of unstructured problems proposed by Kolkman et al. (2005). Whilst, the integration problems are addressed based on different concepts and theories, namely the paradigm lock, epistemic community and bounded rationality. Subsequently, a conceptual framework addressing the problems through the broad perspective of organisation knowledge management is proposed. The framework illustrates an organisation of scientists and decision-makers getting involved in the knowledge management process. It provides for guidance or stepping stone to further take on micro studies of human decision-making as well as decision makers heuristics. – – Die Entwicklung und Durchführung eines übertragbaren Entscheidungshilfesystems (DSS) für das Umweltmanagement oder das Management von natürlichen Ressourcen ist eine große Herausforderung, da die komplexen Fragestellungen sowohl Naturprozesse als auch soziale Prozesse betreffen. Dies macht die Übertragung der wissenschaftlichen Ergebnisse auf die Entscheidungsprozesse schwierig und führte unter Umständen auch zu widersprüchlichen Resultaten. Daher werden holistische und integrierte Ansätze sowohl für das Verständnis der Elemente, die den komplexen Situationen zu Grunde liegen, als auch für die Bearbeitung der Schnittstellen und Integrationsprobleme benötigt, um die Anwendbarkeit und Übertragbarkeit des DSS zu verbessern. Die Zielsetzung dieses Arbeitsberichts ist es in erster Linie die relevante Literatur und den aktuellen Wissensstand zusammenzustellen und zu analysieren, damit der Forschungshintergrund und der Rahmen für das Forschungsprojekt eingerichtet werden können. Das endgültige Ziel des Forschungsprojekts ist es ein übertragbares Entscheidungsfindungsverfahren, das die Integration von Wissensdarstellung und Nutzen (oder soft und hard Systeme) in Bezug auf ein integriertes Hochwassermanagement enthält, zu entwickeln. Dadurch soll die Zusammenarbeit und die Koordination verschiedener Akteuren gefördert werden. Ein theoretischer Ansatz wird in dieser Untersuchung eingesetzt. Das Konzept des Systemischen Denkens wird für das Verständnis des komplexen Entscheidungsfindungssystems, das den komplexen Situationen zu Grunde liegt, verwendet. Die komplexen Entscheidungsprobleme werden auf Grundlage des Konzepts der unstrukturierten Probleme, das auf Kolkman et al. (2005) zurückgeht, analysiert. Dabei werden die Integrationsprobleme nach verschiedenen Konzepten und Theorien, nämlich dem paradigm lock der epistemic community und dem bounded rationality angesprochen. Anschließend wird ein Konzeptionsrahmen vorgeschlagen, der die Probleme durch das Konzept des Organisationswissensmanagements angeht. Dieser Rahmen erläutert die Organisation von Wissenschaftern und Entscheidungsträgern, die am Wissensmanagementprozess beteiligt sind. Er dient als eine Basis für weitere Detailstudien über Entscheidungsfindungsprozesse und Entscheidungsträgerheuristik.
Keywords: 330